The relationship between training, competition satisfaction and burnout in athletes - Zhang, L.; Zhang, L.; Ma, Q. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this study was to examine the relationship between burnout and training/competition satisfaction of Chinese athletes. The Athlete Burnout Questionnaire (ABQ; Raedeke & Smith, 2001) and training/competition satisfaction questionnaire (Zhang & Leung, 2002) were completed by 381 Chinese athletes from 20 different sports (mean age=18.44 years). Results The results indicated that burnouts in Chinese athletes are not serious. Among the three factors contributing to burnout, the score of reduced sense of accomplishment was higher than emotional/physical exhaustion (12.76 vs. 11.75; F=29.12, p=.00), which in turn was higher than sport devaluation (11.75 vs. 10.57; F=41.05, p=.00). Correlation analysis indicated that, all dimensions of burnout were related negatively to training and competition satisfaction. Moreover, a simultaneous multiple regression analysis revealed that all three dimensions of burnout significantly predicted training/competition satisfaction. In order to examine the importance of each subscale of the ABQ in predicting training /competition satisfaction, dominance analysis was employed by taking training/competition satisfaction as the dependent variable and the three subscales of ABQ as independent variables. The findings indicated that 46.74% of the variance could be attributed to a reduced sense of accomplishment, emotional/physical exhaustion accounted for 21.25%, and sport devaluation 32.01%. Discussion These results suggest that burnouts in Chinese athletes are most represented by a reduced sense of accomplishment. In addition, athletes who experienced a burnout were more at risk of having low training and competition satisfaction. It is recommended that future work should attempt to reduce burnouts in athletes in order to heighten the athletes training and competition satisfaction.